2008
DOI: 10.1155/2008/415848
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic Evaluation of Small Renal Masses (I): Pretreatment Management

Abstract: When characterizing a small renal mass (SRM), the main question to be answered is whether the mass represents a surgical or nonsurgical lesion or, in some cases, if followup studies are a reasonable option. Is this a task for a urologist or a radiologist? It is obvious that in the increasing clinical scenario where this decision has to be made, both specialists ought to work together. This paper will focus on the principles, indications, and limitations of ultrasound, CT, and MRI to characterize an SRM in 2008… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 111 publications
0
10
0
Order By: Relevance
“…The reported incidences of benign pathological lesions with a tumor diameter of ≤40 mm were 17.3-23.4% in studies from Western countries (5,6,(19)(20)(21)(22)) and 7.1-15.0% in studies from Asian countries (7,8,23). Fujii et al suggested that one possible reason for the lower incidence of benign pathological findings in Asian than Western countries was the low incidence rate of oncocytoma in Asia (7), which is indistinguishable from RCC using the present imaging modalities (24). The reported incidence rates of oncocytoma in small renal masses were 5.7-10.7% in Western countries (5,6,19-22) but 1.3-2.8% in Asian countries (7,8,23), consistent with the results of the present study (1.5%).…”
Section: Discussionmentioning
confidence: 71%
“…The reported incidences of benign pathological lesions with a tumor diameter of ≤40 mm were 17.3-23.4% in studies from Western countries (5,6,(19)(20)(21)(22)) and 7.1-15.0% in studies from Asian countries (7,8,23). Fujii et al suggested that one possible reason for the lower incidence of benign pathological findings in Asian than Western countries was the low incidence rate of oncocytoma in Asia (7), which is indistinguishable from RCC using the present imaging modalities (24). The reported incidence rates of oncocytoma in small renal masses were 5.7-10.7% in Western countries (5,6,19-22) but 1.3-2.8% in Asian countries (7,8,23), consistent with the results of the present study (1.5%).…”
Section: Discussionmentioning
confidence: 71%
“…However, making a definitive diagnosis in SRM remains difficult. Angiomyolipoma (AML) is typically a solid benign lesion that exhibits fat density on CT scans [12]. However, some renal lesions may contain a very small amount of fat ("minimal fat AML") with microscopic fat and without demonstrable macroscopic fat; these lesions cannot be differentiated from RCCs.…”
Section: Introductionmentioning
confidence: 99%
“…MRI is performed usually during end-expiratory breath-hold and subsequently requires patient cooperation and ability to do so [15,16]. During an MRI, provided there are no contraindications, intravenous gadolinium is administered.…”
Section: Magnetic Resonance Imaging In the Diagnosis Of Srmmentioning
confidence: 99%